2022
DOI: 10.1039/d1nr08038e
|View full text |Cite
|
Sign up to set email alerts
|

Highly luminescent red-emitting In(Zn)P quantum dots using zinc oxo cluster: synthesis and application to light-emitting diodes

Abstract: High quality red-emitting In(Zn)P QDs were synthesized by combining a Zn oxo cluster and seed-mediated continuous growth method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…It is demonstrated that the FWHM of final emission spectrum decreases from 56 to 37 nm, in the meanwhile the emission peak blue shifts more than 10 nm which is attributed to the smaller size (Figure 3d). [ 52 ] Similarly, it is also observed in the investigation reported by Koh et al. and they proposed the effect of Zn‐P complex on size tuning through regulating reactivity of [P] with [In].…”
Section: Challenges For Blue‐emitting Inp Qdssupporting
confidence: 59%
See 3 more Smart Citations
“…It is demonstrated that the FWHM of final emission spectrum decreases from 56 to 37 nm, in the meanwhile the emission peak blue shifts more than 10 nm which is attributed to the smaller size (Figure 3d). [ 52 ] Similarly, it is also observed in the investigation reported by Koh et al. and they proposed the effect of Zn‐P complex on size tuning through regulating reactivity of [P] with [In].…”
Section: Challenges For Blue‐emitting Inp Qdssupporting
confidence: 59%
“…It is demonstrated that the FWHM of final emission spectrum decreases from 56 to 37 nm, in the meanwhile the emission peak blue shifts more than 10 nm which is attributed to the smaller size (Figure 3d). [52] Similarly, it is also observed in the investigation reported by Koh et al and they proposed the effect of Zn-P complex on size tuning through regulating reactivity of [P] with [In]. [29] Therefore, it is crucial to slow down the reaction rate of P(TMS) 3 for avoiding the rapid formation and consumption of monomers thus causing hard preparation of small-size InP QDs.…”
Section: Growth Kineticsmentioning
confidence: 73%
See 2 more Smart Citations
“…Another way to prevent surface oxidation of CQDs is adding additional surface ligands for conformal surface passivate. For InP CQDs, it was reported that zinc complexes form In(Zn)P outer layer that protects the InP core from oxidation even after the washing and redispersion process [ 27 , 28 ]. However, the quantitative analyses on function of zinc complexes in InP CQDs are not fully explores yet.…”
Section: Introductionmentioning
confidence: 99%